Discovering structural complexity and its causes: Breeding aggregations in horseshoe crabs. (September 2018) - Brockmann, H. Jane; St Mary, Colette M.; Ponciano, José Miguel
Abstract : In some species, especially those that form breeding aggregations, males form groups around females vying for fertilizations. These mating groups are often highly variable in size even during a single breeding event. We examined this variation in the American horseshoe crab, Limulus polyphemus, a species in which some females (nesting in pairs) attract additional males (satellites) and spawn in groups whereas others spawn only with their attached male. The observed distribution of group sizes often consists of an overabundance of pairs with no satellite males and groups with large numbers of satellites. We characterized this variation using well-known models of count data, such as the Poisson and negative binomial distributions, and evaluated how operational sex ratio (OSR) and pair density contribute to the observed variation. We complemented this descriptive approach with spatially explicit simulations of the group formation process. By comparing our simulation results to the observed breeding aggregation data, we identified how simple behavioural rules might contribute to the variation we observe. Those rules amount to hypotheses about pair and satellite arrival at the beach and satellite sampling of and choice among pairs. We found that the observed variation could be explained by a consistent high frequency of females that attract satellites in combination with males that sample different fractions of the beach as pair density and OSR vary. Furthermore, our simulations suggested that males are not choosy in joining pairs on the beach, despite variation among pairs in the fertilization success satellites can achieve. This suggests that new insights might come from investigating the costs and benefits of male choice and the sensory mechanisms satellite males use to assess the breeding aggregation before coming ashore. Highlights: Horseshoe crab breeding aggregations vary qualitatively. Mating pair density and OSR explain some variation in aggregation type. Simple changes in mating behaviour predict qualitative variation in aggregations. Spatial modelling reveals that most pairs attract satellites but about 10% do not. Simulations show satellites assess pair density and OSR but join groups at random.